Shape-driven arrest of coffee stain effect drives the fabrication of carbon-nanotube-graphene-oxide inks for printing embedded structures and temperature sensors. Issue 48 (3rd December 2019) - Zhao, Beihan; Wang, Yanbin; Sinha, Shayandev; Chen, Chaoji; Liu, Dapeng; Dasgupta, Abhijit; Hu, Liangbing; Das, Siddhartha
Abstract : Carbon nanotube (CNT) based binder-free, syringe-printable inks, with graphene oxide being used as dispersants, have been designed and developed based on the unique ellipsoidal-particle-shape-mediated arrest of the coffee-stain effect. Abstract : Carbon nanotube (CNT) based binder-free, syringe-printable inks, with graphene oxide (GO) being used as the dispersant, have been designed and developed. We discovered that the printability of the ink is directly attributed to the uniform deposition of the GO–CNT agglomerates, as opposed to the 'coffee-staining' despite these aggregates being micron-sized. The ellipsoidal nature of the micron-scale GO–CNT agglomerates/particles enables these particles to severely perturb the air–water interface, triggering a large long-range capillary interaction that causes the uniform deposition by overcoming the "coffee-stain"-forming forces from the evaporation-mediated flows. We evaluated the properties of this ink and identified a temperature-dependent resistance with a negative temperature coefficient of resistance (TCR) α ranging from ∼−10 −3 to −10 −2 /°C depending on ink compositions. Finally, the printing is conducted on flat and curved surfaces, for developing polymer-ink embedded structures that might serve as precursors to syringe-printable CNT-based nanocomposites, and for fabricating sensor-like patterns that for certain ink compositions demonstrate α ∼ −10 −3 /°C with a large averaged resistance drop (per unit temperature) of −3.5 Ω °C −1 .